UV Light-Induced Degradation of Industrial Silicon HJT Solar Cells: Degradation Mechanism and Recovery Strategies (Journal of Solar Energy Research Updates, 2023)
Abstract: The demand for Silicon heterojunction solar cells (HJT) has significantly grown recently. These solar cells have gained recognition for their remarkable performance, which can be attributed to the exceptional passivation properties of bilayers consisting of intrinsic and doped hydrogenated amorphous silicon. This study investigates alternative recovery methods and looks into the deterioration caused by UV radiation in commercial Silicon HJT solar cells. The carrier lifetimes of the samples were measured before and after the HJT solar cells were exposed to ultraviolet radiation. The findings revealed a decrease in carrier lifetime, iVoc, and iFF, indicating the creation of defects in the bulk of a-Si:H and the interface between c-Si and a-Si:H. It was assessed how SiOx performed as a passivation layer. It has been discovered that SiOx can passivate dangling bonds, increase carrier lifetime and reduce trap density. In addition, recovery techniques like current injection, infrared, light soaking, and annealing were applied. The current injection, infrared, and light soaking treatments were discovered to be able to partially restore the efficiency of the solar cells without the combination of temperature, while annealing was found to be more effective. Additionally, the effects of both short and prolonged exposure to UV are investigated. The HJT solar cells exposed to prolonged UV radiation for an extended period of time could not fully regain their efficiency and displayed irreparable flaws. Overall, this study demonstrates the potential of recovery treatments and passivation techniques in increasing the efficiency of Si HJT solar cells and illuminates the processes underlying ultraviolet-induced deterioration. Overall, this study sheds light on ultraviolet-induced degradation mechanisms and highlights the potential of recovery treatments and passivation techniques in enhancing the efficiency of Si HJT solar cells.